2004
DOI: 10.1001/jama.292.18.2263
|View full text |Cite
|
Sign up to set email alerts
|

Human Monocytic Ehrlichiosis

Abstract: A 56-year-old man with a history of Wegener granulomatosis presented with 6 days of sinus congestion, fever, malaise, myalgias, episcleritis, and a morbilliform rash. An exacerbation of Wegener granulomatosis was the principal concern because of the frequency of flares in that disease. The patient developed acute renal failure, thrombocytopenia, transaminitis, and, finally, severe myocarditis that led to congestive heart failure. Additional historytaking and the evolution of his clinical features led to empiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
41
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 50 publications
4
41
0
4
Order By: Relevance
“…Severe and fatal infection of immunocompetent mice with IOE, however, causes severe tissue damage to multiple organ systems in a setting of a low bacterial burden (26). This observation mirrors what occurs in immunocompetent patients who develop multisystem organ failure without an overwhelming infection (49). Our previous studies demonstrated that resistance to fatal disease is mediated by gamma interferon (IFN-␥) production and CD4…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Severe and fatal infection of immunocompetent mice with IOE, however, causes severe tissue damage to multiple organ systems in a setting of a low bacterial burden (26). This observation mirrors what occurs in immunocompetent patients who develop multisystem organ failure without an overwhelming infection (49). Our previous studies demonstrated that resistance to fatal disease is mediated by gamma interferon (IFN-␥) production and CD4…”
supporting
confidence: 69%
“…Human monocytotropic ehrlichiosis (HME) resembles toxic shock syndrome and is caused by Ehrlichia chaffeensis, a gram-negative, obligately intracellular bacterium that lacks lipopolysaccharide (LPS) and peptidoglycan (30,37,49,52). In mice, inoculation with a high dose of IOE (a monocytotropic Ehrlichia species isolated from Ixodes ovatus ticks in Japan) (46) results in a fatal syndrome that mimics severe HME (26,48).…”
mentioning
confidence: 99%
“…Ehrlichia chaffeensis, the etiologic agent of HME, is an obligately intracellular bacterium that resides in mononuclear phagocytes. HME initially manifests as nonspecific flulike illness and can progress to severe toxic shock-like syndrome with thrombocytopenia, lymphopenia, liver dysfunction, and multi-organ failure (23,32). The presence of extensive inflammation in tissues in the absence of overwhelming bacterial burden in fatal cases of HME suggests that fatal disease is due to immune-mediated pathology (28).…”
mentioning
confidence: 99%
“…Infection is often self-limiting in immunocompetent individuals but can be fatal in immunocompromised, and in some cases apparently immunocompetent, individuals (13). Fatal disease is characterized by flu-like symptoms, thrombocytopenia, lymphopenia, and liver dysfunction (12,14). The ehrlichiae are primarily monocytotropic but can also infect other host cells, including endothelial cells and hepatocytes (15).…”
mentioning
confidence: 99%